WT1 in Adipose Tissue: From Development to Adult Physiology - Kirschner, Karin M.; Scholz, Holger (Frontiers in Cell and Developmental Biology, 2022)
Much of the fascination of the Wilms tumor protein (WT1) emanates from its numerous roles in development and disease. Ubiquitous Wt1 deletion in adult mice causes multiple organ failure including a marked reduction of body fat. WT1 is expressed in fat cell progenitors in visceral white adipose tissue (WAT) supporting a mesothelial origin of these fat depots. WT1 is detected neither in energy storing subcutaneous WAT nor in brown adipose tissue (BAT), which has a prominent role in heat production. Our recent findings indicate that WT1 represses thermogenic genes and maintains the white adipose identity of visceral fat. Wt1 heterozygosity in mice is associated with molecular and morphological signs of browning including elevated levels of uncoupling protein 1 (UCP1) in epididymal WAT. Compared to their wild-type littermates, Wt1 heterozygous mice exhibit significantly improved whole-body glucose tolerance and alleviated hepatic steatosis under high-fat diet. Partial protection of heterozygous Wt1 knockout mice against metabolic dysfunction is presumably related to browning of their epididymal WAT. In the light of recent advancements, this article reviews the role of WT1 in the development of visceral WAT and its supposed function as a regulator of white adipose identity.